Fabrication of Polyacrylonitrile UF Membranes by VIPS Method with Acetone as Co-Solvent - Alexey Yushkin; Alexey Balynin; Mikhail Efimov; Konstantin Pochivalov; Inna Petrova; Alexey Volkov (Membranes, 2022)
For the first time, a systematic study was carried out of the replacement of the low-volatility solvents N-methyl-2-pyrrolidone (NMP) or dimethylsulfoxide (DMSO) with the high-volatility solvent acetone in the casting solution of polyacrylonitrile (PAN). The effect of acetone’s presence in the casting solution on the performance of ultrafiltration membranes fabricated via vapor-induced phase separation (VIPS) was investigated. It was possible to replace 40% of NMP and 50% of DMSO with acetone, which resulted in the reduction of the casting solution viscosity from 70.6 down to 41.3 Pa∙s (20% PAN, NMP), and from 68.3 down to 20.6 Pa∙s (20% PAN, DMSO). It was found that 20 min of exposure to water vapor (relative humidity—85%) was sufficient to govern the phase separation, which was mainly induced by the water vapor. Regardless of the casting solution composition (15 or 20% PAN; DMSO or NMP), all membranes formed via VIPS possessed a sponge-like porous structure. The addition of acetone to the casting solution allowed the reduction of the transport pore size from 35–48 down to 8.5–25.6, depending on the casting solution composition. By varying the acetone content at constant polymer concentration, it was possible to decrease the molecular weight cut-off (MWCO) from 69 to 10 kg/mol. Membranes prepared from 20% PAN solution in an acetone/DMSO mixture had the lowest MWCO of 10 kg/mol with a water permeance of 5.1 L/(m2·h·bar).